Maternal warmth, motivation for engagement in cyberbullying and cyberbullying involvement among undergraduate student - Arshat, Zarinah; Leow, Mandy Zhia Hooi; Tun, Ju Ern; Ahmad Shahril, Nurul Saidatus Shaja’ah (Human Resource Management Academic Research Society, 2022)
This study aims to determine the relationship between maternal warmth, motivation for engagement in cyberbullying and cyberbullying involvement among undergraduate students. By using the cluster random sampling method, a total of 398 respondents were involved in this research. Among all the variables, only total hours spent online, maternal warmth and motivation for engagement in cyberbullying were significantly correlated with cyberbullying involvement. Besides, motivation for engagement in cyberbullying was found to be the only predictor of cyberbullying involvement among students. This study concluded that total hours spent online, maternal warmth and motivation for engagement in cyberbullying were the important factors in influencing the level of adolescents’ cyberbullying involvement. In conclusion, cyberbullying phenomenon can be controlled if the adolescents’ cyberaggression motivation was controlled and they have perceived high maternal warmth.